Maternal knowledge and practices on complementary feeding in a health center in Lambayeque, Peru 2021 - García Casusol, Carmen Rosa Samary (2022)
Objective: Determine the relationship between maternal knowledge and practices on complementary feeding in a health center in Lambayeque, Peru 2021. Method: This research was non-experimental, quantitative, correlational, cross-sectional. The sample consisted of 151 mothers, obtained by StatCalc, from a population of 250. The sampling was simple random probabilistic, the technique used was the survey and the instrument was a questionnaire prepared by Barzola, resulting in 0.059 in the table of concordance, determining its validity, the Kuder Richardson statistical test was also applied with a result of 0.62. Subsequently, descriptive tables were built on the variables studied and the Pearson correlation and determination model was used through SPSS V24 software. The ethical criteria taken into account during the investigation were: respect for people, justice and beneficence. Main results: It was obtained that 63% of the mothers do not know general aspects and characteristics of the complementary feeding provided to their children. Likewise, 68% have inadequate practices on hygiene, preparation, food storage and mother-child interaction, when the variables are correlated, it was found to be significant at the 0.01 level (bilateral), according to Pearson's correlation coefficient. Overall conclusion: There is a high relationship, it is possibly due to the lack of food education that mothers have during the age (8 to 11 months) in which children do not have any scheduled immunizations despite the fact that they must attend monthly until the year for your controls.